Symptom perception in heart failure: a scoping review on definition, factors and instruments. (February 2020) - Santos, Gabrielle Cécile; Liljeroos, Maria; Dwyer, Andrew A; Jaques, Cécile; Girard, Josepha; Strömberg, Anna; Hullin, Roger; Schäfer-Keller, Petra
Background: Symptom perception in heart failure has been identified as crucial for effective self-care that is a modifiable factor related to decreased hospital readmission and improved survival. Aims: To review systematically the heart failure symptom perception literature and synthesise knowledge on definition, description, factors and instruments. Methods: We conducted a scoping review including studies reporting patient-reported symptom perception in adults with heart failure. Structured searches were conducted in Medline, PubMed, Embase, CINAHL, PsychINFO, Web of Science, Cochrane, JBI and grey literature. Two authors independently reviewed references for eligibility. Data were charted in tables and results narratively summarised. Results: The search yielded 3057 references, of which 106 were included. The definition of heart failure symptom perception comprised body listening, monitoring signs, recognising, interpreting and labelling symptoms, and furthermore awareness of and assigning meaning to the change. Symptom monitoring, recognition and interpretation were identified as challenging. Symptom perception facilitators include prior heart failure hospitalisation, heart failure self-care maintenance, symptom perception confidence, illness uncertainty and social support. Barriers include knowledge deficits, symptom clusters and lack of tools/materials. Factors with inconsistent impact on symptom perception include age, sex, education, experiences of living with heart failure, comorbidities, cognitive impairment, depression and symptom progression. One instrument measuring all dimensions of heart failure symptom perception was identified. Conclusion: Heart failure symptom perception definition and description have been elucidated. Several factors facilitating or hampering symptom perception are known. Further research is needed to determine a risk profile for poor symptom perception – which can then be taken into consideration when supporting heart failure self-care.